1983
DOI: 10.1136/thx.38.8.624
|View full text |Cite
|
Sign up to set email alerts
|

Premedication for fibreoptic bronchoscopy.

Abstract: ABSTRACr A randomised, double-blind trial of atropine, atropine plus papaveretum, and atropine plus diazepam given intramuscularly as premedication for fibreoptic bronchoscopy in 60 patients showed no difference between the three regimens as assessed by bronchoscopist or patient. Bronchoscopists frequently attributed a sedative action to atropine alone and their assessment of tolerance and sedation was more optimistic than that of the patients. In a second study comparing intravenous diazepam (10 mg) with sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…We used modified versions of previously reported questionnaires 7,12,13 to assess the patient's, operator's, or nurse's reported outcomes of the bronchoscopy. The patient questionnaire included 19 items investigating the satisfaction with the different parts of the flexible bronchoscopic procedure, the willingness to repeat the procedure if necessary, and the symptoms experienced during the procedure (Table 1 shows the English translation of the questionnaire).…”
Section: Questionnairesmentioning
confidence: 99%
“…We used modified versions of previously reported questionnaires 7,12,13 to assess the patient's, operator's, or nurse's reported outcomes of the bronchoscopy. The patient questionnaire included 19 items investigating the satisfaction with the different parts of the flexible bronchoscopic procedure, the willingness to repeat the procedure if necessary, and the symptoms experienced during the procedure (Table 1 shows the English translation of the questionnaire).…”
Section: Questionnairesmentioning
confidence: 99%
“…The old argument that up to half of the major complications of bronchoscopy are sedation related [7] is not confirmed by several more recent studies. In fact, even after comparing different sedative drugs versus placebo, no difference in the complication rate between sedated and nonsedated patients has been found [8][9][10][11][12][13][14], except for a slight but manageable increase in hypoxaemia risk with the use of midazolam and alfentanil [14] and a prolonged hospital stay after the procedure [10]. In fact, the use of sedation, when compared with placebo, resulted in improved overall tolerance and patient perception of bronchoscopy [9][10][11][12][13][14], reduced cough [8,12,14], and better predisposition of patients to repeating the procedure [10,[12][13][14].…”
mentioning
confidence: 99%
“…Operators often tend to minimise patient discomfort [3][4][5] and, although FB can be performed without sedation [6][7][8], a recent survey revealed that 80% of patients prefer to be sedated during FB [4].…”
mentioning
confidence: 99%